2021
DOI: 10.1021/acsanm.1c03873
|View full text |Cite
|
Sign up to set email alerts
|

SiO2/MXene/Poly(tetrafluoroethylene)-Based Janus Membranes as Solar Absorbers for Solar Steam Generation

Abstract: Water treatment through interface photothermal conversion using solar energy is a sustainable strategy for freshwater supply. Because the preparation method of highly efficient photothermal conversion materials with commercial value is the only way for the industrialization of solar steam generation, the preparation method and the rational design of photothermal materials are particularly important. In this work, the highefficiency photothermal conversion material MXene nanosheets and low thermal conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The difference among the performance of the three evaporators indicates the effect of scaffolding structure and MXene on the evaporation efficiency. CMSK shows an excellent evaporation rate and the largest energy efficiency, being superior to most reported ones (Figure g). , Based on eqs – for the calculation of evaporation efficiency in Section , the high evaporation efficiency of the evaporator is attributed to the high temperature generated on the evaporator surface and the high evaporation rate.…”
Section: Resultsmentioning
confidence: 93%
“…The difference among the performance of the three evaporators indicates the effect of scaffolding structure and MXene on the evaporation efficiency. CMSK shows an excellent evaporation rate and the largest energy efficiency, being superior to most reported ones (Figure g). , Based on eqs – for the calculation of evaporation efficiency in Section , the high evaporation efficiency of the evaporator is attributed to the high temperature generated on the evaporator surface and the high evaporation rate.…”
Section: Resultsmentioning
confidence: 93%
“…It was found that the four kinds of ion concentrations were significantly reduced and the ion concentrations of Na + , Mg 2+ , K + , and Ca 2+ were well below the World Health Organization (WHO) standard for drinking water, indicating that the freshwater condensed by the Janus CNT@PBAT fabric was clean and safe enough for human consumption. The above results indicated that the as-prepared 3D water channel evaporator shows outstanding and stable evaporation rates and salt resistance performance, which are comparable to or even higher than those of the previously reported superhydrophobic Janus solar evaporator, as summarized in Figure f and Table S1. ,, , Moreover, the as-prepared 3D WCE equipped with the Janus fabric had a potentially low cost due to both the renewable and cost-effective cotton fiber and the facile process (shown in Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The Cu@CuO/CG-aero Janus membranes prepared by Zhao et al 246 exhibited an efficient purification performance for wastewater by solar energy, and the results of using the modified membranes to treat wastewater continuously for 6 days showed almost uniform evaporation per day and no fouling, indicating their long-lasting durability. Li et al 247 prepared a SiO 2 /MXene/poly(tetrafluoroethylene) Janus membrane with a removal rate of 99.9% for heavy metal ions and dye contaminants. The temperature change trend was basically the same for various cycles in the cyclic heating-cooling test, which indicated that it has excellent physical and mechanical properties, making it stable and reusable.…”
Section: Application and Research Progress Of Sdie In Practical Water...mentioning
confidence: 99%